Developing an Islamic Values Integration Model in Education: Evidence from a Muslim-Minority Context in Southern Thailand - Issama-ae Jehma; Mahfud Junaedi; Ismail Ismail (Journal of Counseling, Education and Society, 2025)
This study aims to analyze the model of integration of Islamized values in education at Tsanawiyah Buranakarn Suksa School, Yaring, Pattani, Southern Thailand, especially in building religious tolerance education in the school environment. This research uses a case study method with a qualitative approach to gain a deep understanding of the process of integrating Islamic values and tolerance in educational practices, learning, social interaction, and school institutional culture. The findings of the study show that religious tolerance education is not applied as a stand-alone learning material, but is thoroughly integrated through the learning process, teacher examples, social interactions, school activities, habituation, and institutional culture. The values of respect for differences, openness, dialogue, cooperation, and peaceful conflict resolution are instilled through students' real experiences in daily life at school. The successful implementation of the model is supported by inclusive school leadership, teachers' role models in treating students fairly and dialogically, a curriculum that connects religious teachings with social life, a school culture that encourages inclusive interaction, and the support of parents and the community. The contribution of this research lies in the development of understanding that the integration of Islamized values in education can be realized through an educational ecosystem approach that connects religious values, learning, example, school culture, and social life. The model provides the perspective that religious tolerance education will be more effective if it is not positioned as a mere formal program or material, but as an integral part of the overall educational system and culture.